X-ray spectroscopy of massive stellar winds: previous and ongoing observations of the hot star ζ Pup. Issue Volume 14:Issue S346(2019) (August 2018) - Miller, N.; Waldron, W.; Nichols, J.; Huenemoerder, D.; Dahmer, M.; Ignace, R.; Lauer, J.; Moffat, A.; Nazé, Y.; Oskinova, L.; Richardson, N.; Ramiaramanantsoa, T.; et al.
Abstract: The stellar winds of hot stars have an important impact on both stellar and galactic evolution, yet their structure and internal processes are not fully understood in detail. One of the best nearby laboratories for studying such massive stellar winds is the O4I(n)fp star ζ Pup. After briefly discussing existing X-ray observations from Chandra and XMM, we present a simulation of X-ray emission line profile measurements for the upcoming 840 kilosecond Chandra HETGS observation. This simulation indicates that the increased S/N of this new observation will allow several major steps forward in the understanding of massive stellar winds. By measuring X-ray emission line strengths and profiles, we should be able to differentiate between various stellar wind models and map the entire wind structure in temperature and density. This legacy X-ray spectrum of ζ Pup will be a useful benchmark for future X-ray missions.